Positively charged specificity site in cyclin B1 is essential for mitotic fidelity - Christian Heinzle; Anna Höfler; Jun Yu; Peter Heid; Nora Kremer; Rebecca Schunk; Florian Stengel; Tanja Bange; Andreas Boland; Thomas U. Mayer (Nature Communications)
Abstract Phosphorylation of substrates by cyclin-dependent kinases (CDKs) is the driving force of cell cycle progression. Several CDK-activating cyclins are involved, yet how they contribute to substrate specificity is still poorly understood. Here, we discover that a positively charged pocket in cyclin B1, which is exclusively conserved within B-type cyclins and binds phosphorylated serine- or threonine-residues, is essential for correct execution of mitosis. HeLa cells expressing pocket mutant cyclin B1 are strongly delayed in anaphase onset due to multiple defects in mitotic spindle function and timely activation of the E3 ligase APC/C. Pocket integrity is essential for APC/C phosphorylation particularly at non-consensus CDK1 sites and full in vitro ubiquitylation activity. Our results support a model in which cyclin B1’s pocket facilitates sequential substrate phosphorylations involving initial priming events that assist subsequent pocket-dependent phosphorylations even at non-consensus CDK1 motifs.